1995
DOI: 10.1007/bf00201384
|View full text |Cite
|
Sign up to set email alerts
|

The monoclonal antibody JIM19 modulates abscisic acid action in barley aleurone protoplasts

Abstract: Abstract.A panel of hybridoma products generated against pea (Pisum sativum L.) guard-cell protoplasts has been assayed for anti-abscisic acid (ABA) biological activity in barley (Hordeum vulgare L.) aleurone protoplasts. The effects of the antibodies on ABA-induced accumulation of mRNA transcribed from RAB-16, a gene responsive to ABA, were determined. Most of the antibodies, and culture medium, had no effect, but five monoclonal antibodies (MAbs) were found to inhibit ABA-induced RAB-16 gene expression and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…There are several indications that cell wall molecules can influence ABA signalling and sensitivity to exogenous ABA, including an extensin epitope (Wang et al. , 1995), an arabinogalactan‐protein (van Hengel & Roberts, 2003) and a putative family 64 glycosyltransferase (Bown et al.…”
Section: Discussionmentioning
confidence: 99%
“…There are several indications that cell wall molecules can influence ABA signalling and sensitivity to exogenous ABA, including an extensin epitope (Wang et al. , 1995), an arabinogalactan‐protein (van Hengel & Roberts, 2003) and a putative family 64 glycosyltransferase (Bown et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additional indirect in vitro evidence for an ABA receptor complex at the cell surface was provided by surface plasmon resonance studies in conjunction with a protoplast ABA-inducible gene expression assay (Desikan et al, 1999). JIM19 is one of a panel of monoclonal antibodies generated against pea guard cell protoplasts that recognizes a cell surface glycoprotein and can modulate ABA responses in barley aleurone and rice protoplasts (Wang et al, 1995;Desikan et al, 1999). Desikan et al (1999) observed specific binding of plasma membranes to JIM19 that was antagonized significantly by ABA but not by the biologically inactive ABA catabolite phaseic acid.…”
Section: Aba Perception Recognition Site(s)mentioning
confidence: 99%
“…Using surface plasmon resonance in conjunction with flow cytometry, Desikan et al (60) provided indirect evidence for a putative ABA-receptor complex that interacts with a cell-surface glycoprotein. A monoclonal antibody (JIM19) generated against pea guard cell protoplasts specifically binds to plasma membrane glycoproteins and antagonizes ABA-inducible gene expression in rice and barley (60,76). It is noteworthy in this context that PLC is involved in shedding of arabinogalactan proteins by plasma membrane vesicles (77).…”
Section: La 3ϩ and Pld Interaction With Aba Effectors Vp1 And Abi1mentioning
confidence: 99%